2021
DOI: 10.1038/s41467-021-21918-6
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV and SARS-CoV-2 are transmitted through the air between ferrets over more than one meter distance

Abstract: SARS-CoV-2 emerged in late 2019 and caused a pandemic, whereas the closely related SARS-CoV was contained rapidly in 2003. Here, an experimental set-up is used to study transmission of SARS-CoV and SARS-CoV-2 through the air between ferrets over more than a meter distance. Both viruses cause a robust productive respiratory tract infection resulting in transmission of SARS-CoV-2 to two of four indirect recipient ferrets and SARS-CoV to all four. A control pandemic A/H1N1 influenza virus also transmits efficient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 46 publications
(54 reference statements)
5
88
0
1
Order By: Relevance
“…Respiratory particle transmission and viability over long distances are subject to changes in ambient temperature, relative humidity, airflow/ventilation, solar ultraviolet radiation (sunlight), and chemicals leading to evaporation, supersaturation, dilution, or inactivation [49,[254][255][256]. Aerosol transmission, direct contact transmission, and fomite transmission have been experimentally demonstrated in multiple animal models [49,[338][339][340][341][342][343]. Furthermore, studies in non-human primates, and confirmed in humans, demonstrate that infected individuals exhale infectious aerosols, but this is highly variable across individuals and activities [344,345].…”
Section: Laboratory Studies and Modeling Datamentioning
confidence: 99%
“…Respiratory particle transmission and viability over long distances are subject to changes in ambient temperature, relative humidity, airflow/ventilation, solar ultraviolet radiation (sunlight), and chemicals leading to evaporation, supersaturation, dilution, or inactivation [49,[254][255][256]. Aerosol transmission, direct contact transmission, and fomite transmission have been experimentally demonstrated in multiple animal models [49,[338][339][340][341][342][343]. Furthermore, studies in non-human primates, and confirmed in humans, demonstrate that infected individuals exhale infectious aerosols, but this is highly variable across individuals and activities [344,345].…”
Section: Laboratory Studies and Modeling Datamentioning
confidence: 99%
“…Immunohistochemical analysis of lung lobes showed the widespread distribution of SARS-CoV-2 antigen-positive cells; and high levels of virus replication were detected in turbinates, soft palate, lung lobes, and other tissues ( Table 1 ; Shuai et al, 2020 ). The virus can be transmitted between minks via the air over more than 1 m distance ( Kutter et al, 2021 ). Although minks infected in the laboratory did not die like infected farm minks, they lost 10–20% of body weight at around 8 dpi.…”
Section: Minkmentioning
confidence: 99%
“…Additionally, we present first qualitative analyses of the efficiency of transmission, showing that even within one hour transmission can occur at a distance of 200 cm between Syrian hamsters. Whereas several SARS-CoV-2 transmission studies in hamsters and ferrets have been performed, none of these studies were able to differentiate between large and small droplet transmission 14,15,[26][27][28] . In our previous work, specifically designed cage dividers were used to generate an airflow system minimizing large droplet cross-over.…”
Section: Discussionmentioning
confidence: 99%